Identification of a target population for immunisation against East Coast fever in coastal Kenya - Maloo, S.H.; Ngumi, P.; Mbogo, S.; Williamson, S.; Thorpe, W.R.; Rowlands, G.J.; Perry, Brian D. (Elsevier, 2001)
Two experiments were carried out to identify the target population of cattle for immunisation against East Coast fever (ECF) using the infection-and-treatment method. Firstly, a sentinel-calf study was used to determine the age window for ECF immunisation by determining ages at clinical detection of infection with Theileria parva. Six groups of five naive cross-bred (Bos taurus/Bos indicus) male calves, introduced at intervals of 2 months at a mean age of 26 days, were exposed to natural tick challenge on a high ECF-risk, small-holder farm in the coastal lowland, coconut¯cassava agro-ecological zone of coastal Kenya. Secondly, a challenge study evaluated the relationship between the presence of T. parva antibodies and immunity. Ten indigenous adult Zebu cattle and nine Zebu young stock purchased from farmers in the same zone, and eight cross-bred calves (survivors of the sentinel-calf study) were challenged with 10 times the immunising dose of T. parva Marikebuni stock. Twenty-four of these 27 cattle had high antibody titres before challenge. Two cross-bred calves, obtained from an ECF-free area and seronegative to T. parva schizont antigen, also were challenged and used as susceptible controls. Twenty-five (83%) of the 30 sentinel calves contracted ECF over an age range of 36¯116 days (mean 72 days). The remaining five calves died of other causes within 2 months of arrival on the farm. Fourteen of the 25 calves survived the infection and developed antibodies to T. parva. Despite tick control, seven of these 14 calves had a second episode of ECF and two died. In total, 13 of the 25 calves that contracted ECF died. Only one of 19 indigenous Zebu animals developed clinical ECF when challenged with T. parva Marikebuni (mild clinical signs with spontaneous recovery). Of the eight cross-bred survivors from the first experiment, only one succumbed to ECF when challenged and it died. Both susceptible cross-bred calves developed severe clinical signs of ECF and one died. The experimental studies show that in the high ECF-risk areas of the coconut¯cassava zone of coastal Kenya, immunisation against ECF in cross-bred (B. taurus/B. indicus) cattle should be targeted at an early age (preferably within 1¯2 months of birth).